The role of integrated fiscal policy in increasing private sector participation and regional economic growth - Husriah, Husriah; Rahma, Filasti; Supradani, Rias; Sudarnice, Sudarnice (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study analyses the influence of tax incentives, public infrastructure spending, and subsidies on regional economic growth in Baubau City through the mediating role of private sector participation. The main issue concerns the effectiveness of fiscal policy in encouraging private sector involvement to support regional economic development. The research employs a mixed methods approach with an explanatory sequential design, combining quantitative analysis using SEM-PLS and qualitative analysis. Data were collected from 100 respondents, including fiscal officials, micro, small, and medium enterprise actors, and private stakeholders. The findings show that tax incentives, public infrastructure spending, and subsidies significantly affect private sector participation and regional economic growth. Private sector participation also mediates the relationship between the three fiscal instruments and economic growth. The novelty of this study lies in the integrated analysis of these three fiscal instruments and the inclusion of internal tax incentives for civil servants, such as employee additional income, which has rarely been discussed in previous studies. The results emphasize that evidence-based fiscal policy and public–private collaboration is crucial for developing effective and inclusive regional development strategies.